2019
DOI: 10.31080/asag.2019.03.0680
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Analysis of Ginger Production in Surkhet District of Nepal

Abstract: The survey research entitled 'Socioeconomic analysis of ginger production in surkhet district' was conducted during March 2019 to May 2019. The Gurwakot, Bheriganga and Awalching was selected purposefully and sample HHs was selected randomly. A total of 30 HHs were selected as sample from Bheriganga and each 25 from Gurwakot and Awalching. The data was collected through household survey (80HHs), 3 focus group discussion (FGD) and key informant survey (KII). In the sampled HHs, the percentage of male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…87.5 per cent of the respondents involved in farming and most (60.62%) of the respondents had medium sized family ranging from 4-10 members. The finding was in line with the findings of Neupane et al, (2019) for occupation and Somvanshi et al, (2016) for family size of respondents. It was found that majority (42.5%) of the respondents had education up to high school level, 58.76 per cent had marginal size of total land holding (less than 2.47 acre) and 80.00 per cent of the respondents cultivating different horticultural crops had marginal size of total land holding (less than 2.47 acre).…”
Section: Socio-economic Characteristics Of the Respondents Cultivating Horticultural Cropssupporting
confidence: 91%
“…87.5 per cent of the respondents involved in farming and most (60.62%) of the respondents had medium sized family ranging from 4-10 members. The finding was in line with the findings of Neupane et al, (2019) for occupation and Somvanshi et al, (2016) for family size of respondents. It was found that majority (42.5%) of the respondents had education up to high school level, 58.76 per cent had marginal size of total land holding (less than 2.47 acre) and 80.00 per cent of the respondents cultivating different horticultural crops had marginal size of total land holding (less than 2.47 acre).…”
Section: Socio-economic Characteristics Of the Respondents Cultivating Horticultural Cropssupporting
confidence: 91%
“…Some key issues to be addressed are unavailability of quality inputs, improved varieties, lack of modern farm equipment and technical knowledge, fluctuation in market price and insufficient access to market information (Paudel, 2019).These problems hinder farmers to obtain optimum vegetable productivity. Price variations, poor farm gate prices, and a lack of storage facilities are some major issues to be discussed (Parajuli, 2018). Similarly, post-harvest loss of vegetable is nearly 20-50% in Nepal (Devkota et al, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In Rukum, the average maximum temperature is 24°C, the lowest temperature is 13°C, the relative humidity is 79 percent, and the annual rainfall ranges from 1400-3200 mm, making it ideal for vegetable seed production. Out of the total country's vegetable seed production, the Rapti zone contributes 25 to 30 percent with Rukum contributing 60% of seed production (Bhandari, 2019). According to the annual report of the vegetable seed production center Rukum 2076/2077 the production of the seed of onion is about 30-40 kg ropani -1 and bulb production is of var.…”
Section: Introductionmentioning
confidence: 99%